Implementation of the Cigarette Sales to Minors Ban Policy in North Oba District - M. Nur, Nurafni; Arif Mustofa; H. Marsaoly, Osnawati (Journal for Quality in Public Health, 2025)
Government Regulation No. 28 of 2024 concerning Health has set strict rules to prohibit the sale of cigarettes to everyone under the age of 21 (twenty one) years and pregnant women in retail. However, in its implementation, there are still many merchant who sell cigarettes to people under the age of 21 years, both intentionally and unintentionally. This study aims to determine the factors that influence the implementation of the tobacco prohibition policy to people under the age of 21 by seller in North Oba District. This type of research used a cross-sectional approach. This study used a sample of 73 individuals, using simple random sampling. The independent variables were knowledge, attitudes, punishment and policy dissemination. The dependent variable was policy implementation. The results of the study indicate a relationship between knowledge variables and policy implementation (p = 0.001). There is a relationship between attitude variables and policy implementation (p = 0.005). There is a relationship between punishment variables and policy implementation (p = 0.000). There is a relationship between policy dissemination variables and policy implementation (p = 0.000). Merchant knowledge and attitudes towards the regulation prohibiting the sale of cigarettes to people under the age of 21 are still relatively low, so the practice of selling cigarettes to minors still often occurs in North Oba District.